Laparoscopic resection and repair of caesarean scar pregnancy - Elsayed, Mostafa A.; Elbohoty, Shereen Barakat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The presented work is case series over 2 years of caesarean scar pregnancy over 2 years from January 2020 to January 2022 in Zinat Alhayat hospital of maternity in Benha city Egypt. Cases recruited from those attending Zeinat Alhayat maternity hospital in Benha and all case proved to have caesarean scar pregnancy by ultrasonography and quantitative HCG the total number of cases were 15 over a period of two years, most of patients complained about abnormal uterine bleeding in the first trimester with abnormal abdominal pain, all cases prepared for laparoscopy in Zinat Alyayat hospital in Benha and a written consent taken then with general anesthesia pelvis and abdomen explored by laparoscopy and the site of the scar opened with a hook with the aid of a traumatic grasper and then sac evacuated and the old scar resected by laparoscopic scissor. Regarding epidemiological data of patients there were no statistically significant difference in age body weight age or the amount of pain by facial analogue scale of pain. All patients saved and laparoscopy done with an average time of 45 min with no operative or postoperative complications, only one of the cases with severe bleeding required blood transfusion of 2 units of blood because HB was 7.8 g/dl, so laparoscopic treatment of caesarean scar pregnancies is a good option for patients with short operative time and good outcomes without complications.